LITERATURE REVIEW : Intervensi Hydrotherapy Untuk Menyurangi Nyeri Dan Meningkatkan Aktifitas Fungsional Pada Penderita Osteoarthritis Kronis - Inda Harisma, (2020)
Osteoarthritis is a non-inflammatory joint degeneration disorder that occurs in movable joints and weight-bearing joints with specific differentiators to bend the joint cartilage that forms new bones in the bones (osteophytes) such as biochemistry, metabolism, physiology and pathology in joint cartilage. and subcondral bone. Problems that arise due to osteoarthritis when joint pain, joint motion barriers, morning stiffness, crepitation, deformity, gait changes. This review literature aims to analyze the complications of physiotherapy in cases of osteoarthritis. In this problem studio, the boundaries to be discussed are problems and functional limitations. The modality to be applied is hydrotherapy exercises. The results of the literature review show that interventions with hydrotherapy are able to overcome the improvement and improve functional function.